Autorzy:Opracowanie zbiorowe
Wydawnictwo:WSiP
Rok wydania:2014
Uzupełnij tabelę iloczynami odpowiednich sum 4.6 gwiazdek na podstawie 5 opinii

Uzupełnij tabelę iloczynami odpowiednich sum

3Zadanie

 

`*` `x+y` `4-6x` `-3+4y`
`x-5` `x^2+xy-5x-5y` `-6x^2+34x-20` `-3x+4xy+15-20y`
`-3-y` `-3x-3y-yx-y^2` `-12+18x-4y+6xy` `-4y^2-9y+9`
`-x+y` `y^2-x^2` `-4x+6x^2+4y-6xy` `3x-4xy-3y+4y^2`

 

 

`(x-5)*(x+y)=x*x+x*y-5*x-6*y=x^2+xy-5x-5y`

`(x-5)*(4-6x)=x*4+x*(-6x)-5*4-5*(-6x)=4x-6x^2-20+30x=-6x^2+34x-20`

`(x-5)*(-3+4y)=x*(-3)+x*4y-5*(-3)+(-5)*4y=-3x+4xy+15-20y`

`(-3-y)*(x+y)=-3*x-3*y-y*x-y*y=-3x-3y-yx-y^2`

`(-3-y)*(4-6x)=-3*4-3*(-6x)-y*4-y*(-6x)=-12+18x-4y+6xy`

`(-3-y)*(-3+4y)=(-3)*(-3)+(-3)*4y-y*(-3)-y*4y=9-12y+3y-4y^2=-4y^2-9y+9`

`(-x+y)*(x+y)=-x*x-x*y+y*x+y*y=-x^2-xy+yx+y^2=y^2-x^2`

`(-x+y)*(4-6x)=-x*4-x*(-6x)+y*4+y*(-6x)=-4x+6x^2+4y-6xy`

`(-x+y)*(-3+4y)=-x*(-3)-x*4y+y*(-3)+y*4y=3x-4xy-3y+4y^2`